Scalable high-speed random number generation for quantum key distribution system - Tan, Isaac. (2012)
A scalable truly random number generator, based on measuring the phase noise of a distributed feedback laser operating at a low intensity level near the lasing threshold, is presented. The spontaneous emission of photons accounts for the true randomness of the quantum phase noise. The random bit generation rate is limited by the bandwidth of the detector and the laser linewidth. A continuously generated random bit sequence with length of up to 8Gbits passes the standard randomness test(NIST Statistical Test) with a final bit generation rate of 31Mbits/s. Improvements to the experimental setup was made by changing the source to a Superluminescent Diode(SLD). Spontaneous emission of photons is still used as the underlying physical process, which is quantum mechanical in origin, thus accounting for the true randomness of the source. The bandwidth of the photodetector is upgraded to 1GHz. Data testing is still being carried out to get proven results that has sequences of higher than 108 bits and acquired without the use of hashing.